Digital Objects in the Design of Digital Libraries: How Can They Support Education? - Nergiz Ercil Çağıltay; Kürşat Çağıltay (Türk Kütüphaneciliği)
The introduction of “reusable learning objects” is a very important development in using object-oriented approaches for on-line education. Similarly, the use of object-oriented approaches to develop “digital objects” is beginning to impact digital libraries. The purpose of this study is to examine the common issues of both developments in the context of reusable learning objects and to demonstrate the importance of digital libraries in online education.